2017
DOI: 10.1177/1524838017708783
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and the Risk for Criminal Justice Involvement and Victimization Among Homeless Individuals: A Systematic Review

Abstract: Homeless individuals are at higher risk of criminal justice involvement (CJI) and victimization compared to their housed counterparts. Exposure to childhood maltreatment (CM; e.g., abuse, neglect) is one of the most significant predictors of CJI and victimization among homeless populations. The aim of this systematic review was to synthesize current knowledge regarding the relationship between CM and CJI and victimization among homeless individuals. Guided by the preferred reporting items for systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 58 publications
2
12
0
1
Order By: Relevance
“…These findings are in line with a growing body of research confirming that a history of ACEs is associated with subsequent higher rates of CJI and victimization among homeless adolescents and adults, regardless of other important factors. 6 These results also provide support for prior studies indicating that exposure to ACEs has an enduring negative effect on brain functioning and physical and mental health 35,36 and that the standard mental health care for individuals with psychiatric illnesses may not be sufficient for those with histories of ACEs (see 27 ). Continued exposure to victimization and CJI may hinder recovery from mental illnesses and inhibit an individual's ability to transition out of homelessness.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These findings are in line with a growing body of research confirming that a history of ACEs is associated with subsequent higher rates of CJI and victimization among homeless adolescents and adults, regardless of other important factors. 6 These results also provide support for prior studies indicating that exposure to ACEs has an enduring negative effect on brain functioning and physical and mental health 35,36 and that the standard mental health care for individuals with psychiatric illnesses may not be sufficient for those with histories of ACEs (see 27 ). Continued exposure to victimization and CJI may hinder recovery from mental illnesses and inhibit an individual's ability to transition out of homelessness.…”
Section: Discussionsupporting
confidence: 74%
“…Our recent systematic review of 20 studies on the association between childhood maltreatment and subsequent CJI and victimization among homeless individuals indicated that experiences of childhood maltreatment, and in particular childhood physical and sexual abuse, are associated with increased risk of both CJI and victimization among homeless persons. 6 This association was significant regardless of important factors such as demographic characteristics (e.g., age, ethnicity, gender), diagnosis of psychiatric disorders, problems with family, age first living on own, deviant subsistence strategies, deviant peers, and substance use. 6 Various factors may contribute to these heightened risks.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Zudem kommt es gehäuft bei Personen auf der Straße, die frühkindliche Traumaerfahrungen haben, gehäuft zu erneuten Diskriminierungs- und Gewalterlebnissen [ 18 , 19 ]. Häufig erwarten Menschen in Wohnungslosigkeit basierend auf diskriminierenden Vorerfahrungen erneuter Stigmatisierung auch in Einrichtungen des Gesundheitssystem ausgesetzt zu sein und meiden dieses; erhebliches Misstrauen in die Behandlung kann daraus resultieren [ 2 , 22 , 35 ].…”
Section: Belastende Lebensereignisse Und Andere Barrierenunclassified
“…2,3 Another important term is non-accidental trauma: action resulting from an act of omission, direct or indirect action that results in harm to the child or impairs his/her health and physical, mental or emotional development. 5 In addition to being a public health problem, exposure to child abuse is associated with negative long-term consequences, including involvement with the criminal system 6 and recurrent use of mental health services. 7 The Brazilian Penal Code foresees, in Article 136, the crime of child abuse and since the implementation of the Child and Adolescent Statute, through the Federal Law No.…”
Section: Introductionmentioning
confidence: 99%